The contribution of distinct subregions of the ventromedial frontal cortex to emotion, social behavior, and decision making. - Rudebeck, P; Bannerman, D; Rushworth, M (2008)
Damage to the ventromedial frontal cortex (VMFC) in humans is associated with deficits in decision making. Decision making, however, often happens while people are interacting with others, where it is important to take the social consequences of a course of action into account. It is well known that VMFC lesions also lead to marked alterations in patients' emotions and ability to interact socially; however, it has not been clear which parts of the VMFC are critical for these changes. Recently, there has been considerable interest in the role of the VMFC in choice behavior during interpersonal exchanges. Here, we highlight recent research that suggests that two areas within or adjacent to the VMFC, the orbitofrontal cortex (OFC) and the anterior cingulate cortex (ACC), may play distinct but complementary roles in mediating normal patterns of emotion and social behavior. Converging lines of evidence from human, macaque, and rat studies now suggest that the OFC may be more specialized for simple emotional responses, such as fear and aggression, through its role in representing primary reinforcement or punishment. By contrast, the ACC may play a distinct role in more complex aspects of emotion, such as social interaction, by virtue of its connections with the discrete parts of the temporal lobe and subcortical structures that control autonomic responses.